Loss of Human Tyrosinase DOPA Oxidase Activity in Artificial M374 Arg and M 374 Lys Mutants - Behzadi Andouhjerdi, Roudabeh; Sadeghizadeh, Majid (Archives of Advances in Biosciences, 2017)
Tyrosinase (Ec: 1.14.18.1) is a copper - containing enzyme which is distributed in all domains of life such as prokaryote, eukaryote, mammals, invertebrates and plants. Tyrosinase catalyzes the oxidation of monophenols to diphenols and diphenols to o-quinones . The tyrosinase crystallographic data shows two histidine -rich regions named CuA and CuB. A loop containing residues M374, S375 and V377 connects the CuA and CuB Centers. This loop is essential for stability of the enzyme. In this study, site directed mutagenesis was used for the replacement of M374 by Arginine and Lysine.in synthesized cDNA cloned in pET 28b (+) . These mutations don't affect the orientation of the Histidin 367(H367) side chain, resulting in loss of activity.